Refractory arterial hypertension: clinical manifestations and controversies - Yuriy I. Karpenko; Saber Garmazi (Kazimierz Wielki University, 2015)
Karpenko Yuriy I., Garmazi Saber. Refractory arterial hypertension: clinical manifestations and controversies. Journal of Education, Health and Sport. 2015;5(11):238-244. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33900 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A238-244 https://pbn.nauka.gov.pl/works/669685 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015.   Refractory arterial hypertension: clinical manifestations and controversies   Karpenko Yuriy I., Garmazi Saber   Odessa National Medical University, Odessa, Ukraine       Abstract   The study was aimed to assess the clinical manifestations in patients with refractory hypertension. There was demonstrated that refractory arterial hypertension is characterized with hyperactivation of sympathetic nervous system. Patients with RAH used 4,6 ± 0,2  medications to control the pressure. The most common combinations are the combination of blockers, ACE inhibitors and diuretics, ACE inhibitors and diuretics, and, ACC, more rarely, patients received a combination of ARB and a diuretic ACC. Every third patient in therapy included 4 or more antihypertensive drugs, that is, there was a polypharmacy.  However the combination of used medications and their dosage regimen does not achieve significant clinical effect.   Key words: arterial hypertension, medication resistance, diagnostics, monitoring.